Kajian Hukum Islam terhadap Praktik Mappajak (Sewa Menyewa) Pohon Cengkeh di Desa Bonto Salama Kabupaten Sinjai - Rosmi Andini; Muhammad Hasibuddin; Muhammad Akil (Universitas Muslim Indonesia, 2022)
The study aims to investigate the mechanism of mappajak (lease) practice of clove trees in Bonto Salama Village and analyze the Islamic law perspective on mappajak (lease) practice of clove trees in the area. This qualitative research sources data from the village head and involved parties. Data collection techniques include observation, interview, and documentation. The collected data is processed through editing, organizing, and finding the results and then analyzed using the inductive method, followed by a conclusion. The study reveals that the mappajak (lease) practice of clove trees in Bonto Salama Village is not valid according to Islamic law because it does not fulfill one of the pillars of ijarah (lease), namely benefits. The benefit gained from mappajak (lease) of clove trees is in the form of material (clove fruit), while ijarah (lease) is a contract that transacts a property to be taken its benefit according to its function, not to take the material produced. Furthermore, the mappajak (lease) practice of clove trees in Bonto Salama Village involves uncertainties in terms of profit and loss before the harvest, as it only relies on estimation, which may cause regret, dispute, or even litigation in the future